ANTIBODY FORMATION IN VOLUNTEERS FOLLOWING INJECTION OF PNEUMOCOCCI OR THEIR TYPE-SPECIFIC POLYSACCHARIDES - Heidelberger, Michael (The Rockefeller University Press, 1946)
1. A modification of the microanalytical quantitative precipitin method, five to ten times as sensitive as the older procedure, has been used to measure the type-specific antibody response in human beings. Injections of type-specific pneumococci or equivalent amounts of their type-specific polysaccharides led to comparable antibody production. In general, the few hundredths of a milligram of polysaccharides injected functioned as extraordinarily powerful antigens. 2. Subcutaneous injections of the polysaccharides were as effective as intracutaneous, and the resulting antibody levels, which were highly variable individually, remained relatively constant for 5 to 8 months, gradually tapering off during periods of observation that exceeded 2 years in some instances. 3. After the injection of several type-specific polysaccharides widely diverse combinations of selective and non-selective responses were observed. 4. Booster doses had little or no effect in increasing circulating antibody, even after 2 years. A tentative explanation is given of this unexpected result. 5. Possibly because they frequently harbor pneumococci, normal human beings appear to be in serological equilibrium with the C-antigen of pneumococcus, since in most instances the quite appreciable anti-C content of their sera remained relatively constant during periods of a year or longer. Many of the sera also contained antibody to S VII.